THE EFFECT OF BUSINESS RISK, ASSET STRUCTURE, SALES GROWTH, AND LIQUIDITY ON THE FINANCIAL PERFORMANCE OF MINING COMPANIES - Rosvita Anggreinauli Br Silaban; Siti Dini; Jakcyca Melyana Saputra (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background :Thisresearch aims to find out how business risk, asset structure, liquidity, and sales growth influence the financial performance of mining companies listed on the Indonesian stock exchange for the 2018-2021 period.Method :researchers used SPPS version c26, processed cdata of 22 companies with a total sample of 33 data. Data collection was taken using purposive sampling method by taking samples that had been determined based on certain criteria. Result:The results of this study indicate that the partial test (T test) shows thatbusiness risk, asset structure, liquidity and sales growth have a significant effect on financial performance and in a simultaneous test (CF test) have a simultaneous and significant effect on financial performance.